Studi Literatur Sistem Penilaian Esai Otomatis Pada E-Learning Dengan Algoritma Winnowing - Amir Salim Khairul Rijal; Billy Hendrik (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Such quick change in information technology and computers have required changes in the educational paradigm, particularly in teaching and learning methods. Computer applications are software services that use computers as the medium. Programming language is the language used in computing to create programs. An algorithm, a systematic sequence of steps, is used to solve a problem, and an example of one of these is the Winnowing algorithm. The Winnowing algorithm is a document fingerprinting method that utilizes hashing to detect text similarities. In an essay exam, an instructor must carry out a manual assessment by checking and correcting each participant's answers. Currently, automatic assessment is still generally limited to multiple choice questions. The purpose of this study is to investigate the extent to which previous studies have examined the assessment of essay questions using the Winnowing algorithm. The results of the study indicate that the application of the Winnowing algorithm in automatic evaluation of essay responses on online learning platforms (e-learning) provides good and stable results, and has a high degree of accuracy.